Mastering Ansible : effectively automate configuration management and deployment challenges with Ansible 2.7 - Freeman, James; Keating, Jesse (Packt Publishing, 2019)
Automation is essential for success in the modern DevOps world. Ansible provides a simple yet powerful automation engine to tackle complex automation challenges This book provides you with the knowledge you need to understand how Ansible 2.7 works at a fundamental level and leverage its advanced capabilities.